Structural Evolution of Hydrothermally Derived Reduced Graphene Oxide - Hsin-Hui Huang (Nature Portfolio, 2018)
Abstract Hydrothermal reduction is a promising approach for graphene oxide (GO) reduction since it is environmentally friendly, simple, and cost effective. We present a detailed study of structural changes occurring in graphene oxide during the reduction process. The correlations between the interlayer spacing, chemical states, work functions, surface morphology, level of disorders, the number of layers, and processing time are elucidated. The results reveal that GO flakes remain in the early stage of the reduction process and that they are fully reduced after a 4-h hydrothermal treatment. With an increase in the reduction time, the resulting product, i.e., reduced graphene oxide, has a low oxygen content, small interlayer spacing, and crumbled and wrinkled structures. We are convinced that these properties can be tuned to a desired level for various applications.